Enrichment Nature of Ultrapotassic Rocks in Southern Tibet Inherited from their Mantle Source. (10th July 2021) - Li, Weikai; Yang, Zhiming; Chiaradia, Massimo; Zhou, Limin; Hou, Zengqian
Abstract: Post-collisional ultrapotassic rocks (UPRs) in the Tibetan Plateau exhibit extreme enrichment in incompatible elements and radiogenic isotopes. Such enrichment is considered to be either inherited from a mantle source or developed during crustal evolution. In this study, to solve this debate we combined mineral textures and in situ geochemical composition of clinopyroxene phenocrysts in UPRs from southern Tibet to reveal their crustal evolution, enrichment cause and constrain metasomatism in their mantle source. Results show that the UPRs experienced an array of crustal processes, i.e., fractional crystallization, mixing, and assimilation. Fractional crystallization is indicated by decreases in Mg# and Ni and enrichment in incompatible elements (e.g. rare earth element (REE), Sr, Zr) toward the rims of normally zoned clinopyroxene phenocrysts (type-I). Magma mixing is evidenced by the presence of some clinopyroxene phenocrysts (type-II, -III) showing disequilibrium textures (e.g. reversed and overgrowth zoning), but in situ Sr isotope and trace element analysis of those disequilibrium zones indicate that late-stage recharged mafic magmas are depleted ( 87 Sr/ 86 Sr: 0.70659–0.71977) compared with the primitive ultrapotassic magmas ( 87 Sr/ 86 Sr: 0.70929–0.72553). Assimilation is revealed by the common presence of crustal xenoliths in southern Tibetan UPRs. Considering the much lower 87 Sr/ 86 Sr values (0.707759–0.709718) and incompatible element contents of these crustal xenoliths relative to their host UPRs, assimilation should have resulted in geochemical depletion of southern Tibetan UPRs rather than enrichment. The diluting impact of both assimilation and mixing is also supported by the modeling results based on the EC-E′RAχFC model combining the growth history of clinopyroxene. Trace elements ratios in clinopyroxenes also imply that the mantle source of southern Tibetan UPRs suffered an enriched and carbonatite-dominated metasomatism. Thus, we conclude that enrichment of southern Tibetan UPRs was inherited from the mantle source.